The Mechanical Designing Process of Proposed Ventilation System For Home Environments - Syaifoelida F.; Kumar S.U.; Jati E.; Hamdan A.M.M. (Institute of Electrical and Electronics Engineers Inc., 2024)
The research began with general idea to look regards to ventilation system performance in Malaysia. Ventilation is the mechanical system in a building that acquires 'new' open air and evacuates the 'defiled' indoor air. Ventilation system utilized to control disclosure to airborne contaminants. It is usually use to evacuate contaminants, for example, exhaust, cleans, and vapours. There are fundamental factors that need to be considered. The customer criteria were collected in Klang Valley through survey and interview. The conceptual design was selected by using morphological diagram and was translated to SOLIDWORK. There are four conceptual designs were generated. The confirmation result was gained by using Ansys, to stimulate, to run and able to verify that this product design will run automatically when the enclosed room temperature at 27C to 30C. Objective to reduce the waste of electricity and maintain the enclosed room temperature. 2023 IEEE.